The Influence of Different Recycling Scenarios on the Mechanical Design of an LED Weatherproof Light Fitting - Camañes, Víctor (Materials (Basel), 2014)
This paper analyzes the high relevance of material selection for the sustainable development of an LED weatherproof light fitting. The research reveals how this choice modifies current and future end of life scenarios and can reduce the overall environmental impact. This life cycle assessment has been carried out with Ecotool, a software program especially developed for designers to assess the environmental performance of their designs at the same time that they are working on them. Results show that special attention can be put on the recycling and reusing of the product from the initial stages of development.